KINERJA PUSTAKAWAN DALAM PEMBERIAN PELAYANAN PUBLIK PADA DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI SUMATERA SELATAN - Hendrasmo, Ignasius; Wijaya, Arie (LPPM STISIP IMAM BONJOL, 2025)
This research aims to analyze and explain the performance of librarians in providing public services at the South Sumatra Province Library and Archives Service and explain the factors inhibiting the performance of librarians in providing public services. The low competency of human resources for librarians and the lack of number of librarians in the Soeman HS public library which is managed by the South Sumatra Province Library and Archives Service means there is an imbalance in the number of services available and the amount of workload. The research method used is a qualitative approach. Data collection techniques include interviews, observation and documentation. while the research informants included by the researchers were 12 (twelve) people. The results of this research explain that the performance of librarians in providing public services at the South Sumatra Province Library and Archives Service is quite good in accordance with their main duties and functions. However, in the context of Human Resources, there is still a need for qualified functional librarians through appointments made by the Regional Government or from librarian training with the aim of improving services at the South Sumatra Province Library and Archives Service.